1997
DOI: 10.1242/dev.124.23.4811
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dlx-1 and Dlx-2 genes in patterning of the murine dentition

Abstract: The molecular events of odontogenic induction are beginning to be elucidated, but until now nothing was known about the molecular basis of the patterning of the dentition. A role for Dlx-1 and Dlx-2 genes in patterning of the dentition has been proposed with the genes envisaged as participating in an ‘odontogenic homeobox gene code’ by specifying molar development. This proposal was based on the restricted expression of the genes in molar ectomesenchyme derived from cranial neural crest cells prior to tooth in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…The HOMF family is composed of homeodomain transcription factors, including Dlx and Msx, both of which are important factors necessary for tooth development. Deletion of Dlx1 and Dlx2 from the mouse genome results in the loss of maxillary molars (45), whereas the expression of Dlx5 and Dlx6 compensates for this loss and allows molar development in the mandibles of these animals (reviewed in ref 46). A Dlx3 mutation was demonstrated to cause defective dental enamel (amelogenesis imperfecta) and enlarged pulp chambers (taurodontism) in humans (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HOMF family is composed of homeodomain transcription factors, including Dlx and Msx, both of which are important factors necessary for tooth development. Deletion of Dlx1 and Dlx2 from the mouse genome results in the loss of maxillary molars (45), whereas the expression of Dlx5 and Dlx6 compensates for this loss and allows molar development in the mandibles of these animals (reviewed in ref 46). A Dlx3 mutation was demonstrated to cause defective dental enamel (amelogenesis imperfecta) and enlarged pulp chambers (taurodontism) in humans (47).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemistry, Vol. 45 was previously identified as an MMP-20 substrate (41), so it served as the positive control. SDS-PAGE analysis demonstrated that type V, but not type III, collagen was cleaved by MMP-20 (Figure 5, top panel).…”
Section: Mmp-20 Expression and Substrate Specificitymentioning
confidence: 99%
“…In addition to Fgf genes , we also identified Matrix metalloproteinase-20 ( Mmp-20 ) that has been shown to be involved in tooth development ( Figure 2b ; Supplementary Tables 1k and 1m ). (Thomas and Sharpe, 1998; Thomas et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to Fgf genes, we also identified Matrix metalloproteinase-20 (Mmp-20) that has been shown to be involved in tooth development (Figure 2b; Supplementary Tables 1k and 1m). [45,46]. The retractable sharp tiger claws are an important tiger adaptation critical for predation.…”
Section: Genome Annotationmentioning
confidence: 99%
“…A different member of the homeodomain family of transcription factors, Distal-less homeobox2 (Dlx2), is expressed in the cementum layer and targeted null mutation of this gene cause disruption of tooth development in mice (Thomas et al, 1997). A transgenic mouse overexpressing Dlx2 in neural crest cells demonstrates tooth abnormalities like incisor crossbite, shortened tooth roots, increased cementum deposition, periodontal ligament disorganization and osteoporotic alveolar bone (Dai et al, 2017).…”
Section: Mouse Models With Increased Apoptosismentioning
confidence: 99%